2017
DOI: 10.1523/jneurosci.3888-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Zic-Proteins Are Repressors of Dopaminergic Forebrain Fate in Mice andC. elegans

Abstract: In the postnatal forebrain regionalized neural stem cells along the ventricular walls produce olfactory bulb (OB) interneurons with varying neurotransmitter phenotypes and positions. To understand the molecular basis of this region-specific variability we analyzed gene expression in the postnatal dorsal and lateral lineages in mice of both sexes from stem cells to neurons. We show that both lineages maintain transcription factor signatures of their embryonic site of origin, the pallium and subpallium. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…The anti-TH antibody recognized the TH which is specifically expressed in dopaminergic neurons. This antibody stained a subpopulation of mature neurons in the glomerular layer of the olfactory bulb in a pattern similar that has been observed in previous studies (de Chevigny et al, 2012;Qin, Ware, Waclaw, & Campbell, 2017;Tiveron et al, 2017).…”
Section: Primary Antibody Characterizationsupporting
confidence: 84%
See 2 more Smart Citations
“…The anti-TH antibody recognized the TH which is specifically expressed in dopaminergic neurons. This antibody stained a subpopulation of mature neurons in the glomerular layer of the olfactory bulb in a pattern similar that has been observed in previous studies (de Chevigny et al, 2012;Qin, Ware, Waclaw, & Campbell, 2017;Tiveron et al, 2017).…”
Section: Primary Antibody Characterizationsupporting
confidence: 84%
“…With the anti‐CalR and anti‐CalB antibodies, we stained two specific sub‐populations of mature neurons within the glomerular layer of the olfactory bulb with a similar pattern as obtained in previous studies (de Chevigny et al, ; Tiveron et al, ).…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Vax1 mRNA was induced at low levels at 1 day postelectroporation (dpe) when most GFP positive cells were transit amplifying precursors [TAPs, (Boutin et al, 2008); Figure 1B]. Expression strongly increased at 2dpe and remained stably high at 4dpe, when most cells were migratory neuronal precursors, before steeply decreasing at 7dpe when cells arrived in the OB and emigrated from the RMS to invade the granule cell (GCL) and the glomerular (GL) layers (Tiveron et al, 2017). In comparison, isolates from dorsally electroporated brains showed no obvious Vax1 mRNA expression over all analyzed time points ( Figure 1B).…”
Section: Vax1 Is Expressed In a Ventro-dorsal Gradient Along The Latementioning
confidence: 99%
“…It has been shown that Gli1 activation by Sonic Hedgehog (SHH) is necessary to generate Calbindin-expressing periglomerular neurons (CB-N) in the ventral aspect (Ihrie et al, 2011). Moreover, the zincfinger transcription factors (TF) Zic1 and Zic2 act as inducers of Calretinin (CR)-expressing GABAergic interneurons in the dorso-septal region (Tiveron et al, 2017). However, the high diversity of the postnatal generated interneuron subtypes suggests that more complex molecular cascades and cross regulatory interactions are put in place to define the stem cell compartment at the necessary resolution.…”
Section: Introductionmentioning
confidence: 99%